Factors associated with healthcare workers willingness to participate in disasters: a cross-sectional study in Sana’a, Yemen - Karuthan Chinna; Weiam Al-Hunaishi; Victor CW Hoe (BMJ Open)
Objectives Willingness to participate in disasters is usually overlooked and not addressed in disaster preparedness training courses to ensure health service coverage. This will lead to issues during the disaster’s response. This study, therefore, aims to assess healthcare workers willingness to participate in biological and natural disasters, and to identify its associated factors.Design This is a cross-sectional study using a self-administered questionnaire. The questionnaire was distributed to 1093 healthcare workers. The data were analysed using multiple logistic regression with significance level p<0.05. Ethical clearance and consent of the participants were duly obtained.Setting In three public hospitals that provide tertiary-level healthcare in Sana’a City, Yemen.Participants There were 692 nurses and doctors (response rate 63.3%) completed the questionnaires.Results Almost half of the participants 55.1% were nurses and 44.9% were doctors. The study found that self-efficacy was associated with willingness to participate in disaster response for any type of disasters (OR 1.319, 95% CI 1.197 to 1.453), natural disasters (OR 1.143, 95% CI 1.069 to 1.221) and influenza pandemic (OR 1.114, 95% CI 1.050 to 1.182). The results further show that willingness is associated with healthcare workers being young, male and having higher educational qualifications.Conclusion Self-efficacy has been found to be an important factor associated with willingness. Improving self-efficacy through training in disaster preparedness may increase willingness of healthcare workers to participate in a disaster.